Pemahaman Mahasiswa Fakultas Bahasa dan Sastra Universitas Nasional terhadap Pancasila sebagai Ideologi - Haichal Fathin Mauludin; Nadya Alya Hakim; Revan Kurniawan; Icha Alena Putri; Muhammad Rizky Al-Faris; Mohammad Hafiz; Muhammad Faizal Alfitra Salam; Mochdar Soleman (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Pancasila is the foundation of the Indonesian state and the national ideology that guides social, national, and state life. Globalization and rapid technological development have created challenges in understanding and implementing Pancasila values, particularly among university students. This study aims to examine students' perspectives on Pancasila as the state ideology, its relevance to student life, the challenges of applying its values, and their implementation in everyday life. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving seven students from the Korean Language, Japanese Literature, and English Literature study programs at Universitas Nasional. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that most students view Pancasila as the foundation of the state, a guide for life, and a unifying force that remains relevant. Its values are implemented through tolerance, deliberation, cooperation, respect for diversity, and discipline in campus life